Phonetic interpretation (Cambridge University Press, 2003)
This study presents innovative work from four core areas: phonological representations and the lexicon; phonetic interpretation and phrasal structure; phonetic interpretation and syllable structure; and phonology and natural speech production. Written by experts in the fields of phonetics, phonology and speech perception, the chapters in this volume use a wide range of laboratory and instrumental techniques to analyze the production and perception of speech. They explore the relationship between the sounds of speech and the linguistic organization that lies behind them.